2008
DOI: 10.4049/jimmunol.180.6.3990
|View full text |Cite
|
Sign up to set email alerts
|

Sporozoite-Mediated Hepatocyte Wounding Limits Plasmodium Parasite Development via MyD88-Mediated NF-κB Activation and Inducible NO Synthase Expression

Abstract: Plasmodium sporozoites traverse several host cells before infecting hepatocytes. In the process, the plasma membranes of the cells are ruptured, resulting in the release of cytosolic factors into the microenvironment. This released endogenous material is highly stimulatory/immunogenic and can serve as a danger signal initiating distinct responses in various cells. Thus, our study aimed at characterizing the effect of cell material leakage during Plasmodium infection on cultured mouse primary hepatocytes and He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
1
24
1
Order By: Relevance
“…In line with this result, it has been demonstrated previously that MyD88-deficient C57BL/6 mice have a higher hepatic parasite load than WT animals (49). In contrast to the published data, we did not observe any difference in the development of liver-stage parasites between WT and MyD88 Ϫ/Ϫ (or TLR2/ 4 Ϫ/Ϫ ) mice.…”
Section: Discussioncontrasting
confidence: 57%
“…In line with this result, it has been demonstrated previously that MyD88-deficient C57BL/6 mice have a higher hepatic parasite load than WT animals (49). In contrast to the published data, we did not observe any difference in the development of liver-stage parasites between WT and MyD88 Ϫ/Ϫ (or TLR2/ 4 Ϫ/Ϫ ) mice.…”
Section: Discussioncontrasting
confidence: 57%
“…LPS suppressed glucose production in hepatocytes through the TLR4/ MyD88/NF-kB pathway (38). In Plasmodium-infected hepatocytes, MyD88 was required for NF-kB activation and inducible nitric oxide synthase expression (39). Here, we showed that elevated hepatic MyD88 was involved in the growth and metastasis of HCC cells.…”
Section: Discussionmentioning
confidence: 61%
“…BAY-11 blocks NFB activity by suppressing the phosphorylation of IB-␣ and has been previously used in several studies to demonstrate NFB involvement in a range of inflammatory contexts. [18][19][20][21][22] When tested at 3 and 30 mol/ L, it was apparent that BAY-11 was an efficient blocker of NF-B signaling, at the higher concentration, as measured by its ability to inhibit BLP-induced CCL3 expression ( Figure 4A). In addition, 30 mol/L BAY-11 blocked the reduction in expression of CCR2 ( Figure 4B) as well as CCRs 1 and 5 (data not shown).…”
Section: Nuclear Factor (Nf)b May Be Involved In Chemokine Receptor Dmentioning
confidence: 99%